Characteristics, audience reception and challenges in Malaysian animation / Mohd Amir bin Mat Omar - Mat Omar, Mohd Amir (2015)
The creative content industry in Malaysia is a growing and developing business. Animation, being part of the creative industry, is also seeing a rise with the increasing number of studios being set up and the increase in numbers of animated series and films being produced. Facing powerhouses such as Japan and the United States, Malaysian animation content finds itself sandwiched in between foreign programs in channels such as Disney, Nickelodeon and Cartoon Network, though better opportunities may be found through local stations. With such an abundance of animated series and films, it is a challenge for Malaysian animation content to stand out as a product of Malaysia compared to anime from Japan and American cartoons. Furthermore, audience reception towards foreign titles has overshadowed locally-produced animation for quite some time. The Malaysian animation industry is at a point where the opportunities have been presented, government support is apparent, technologies have been made available and media becoming more and more individualized. Nowadays, producing animation has become more simplified through usage of computer technology and has allowed more room for creativity and imagination. All of this has led towards the four objectives of this research 1) to provide a descriptive list of animation produced from 1978 to 2010, 2) to analyze the tangible, intangible, verbal and non-verbal characteristics that define Malaysian animation, 3) to analyze the reception towards Malaysian animation among local and foreign audiences and 4) to identify challenges faced by the animation industry and, in turn, to recognize the future direction planned by relevant bodies to overcome these issues. This study uses the structuralist-semiotic analysis to identify Malaysian animation characteristics, focus group interviews to analyze audience reception and in-depth interviews to identify the challenges and recognize the future direction of Malaysian animation. Results of this research explain the elements that make Malaysian animation, Malaysian, and describes the perceptions and reactions of both local and foreign audiences towards Malaysian animation and also describe and explain the challenges faced by the Malaysian animation industry.